(untitled) (Fiep Bulletin - online, 2014)
The shot put and the javelin throw are a complex technical discipline that requires a proper execution of the kinetic chain movements, so it is very difficult to determine whether it will be the globe thrower when it starts work with the beginners. In the age of modern technology, when biomechanical analysis is used in prediction of achieving top results in sports, it is desirable to apply the anthropometrical methods in the training process of young children. From this, a need is derived to further explore the morphological features of shot put and javelin throwers, and this research therefore strived to establish a relation between the anthropometric dimensions and the results achieved in shot put and javelin throw. The age of the examinees was 15 years of age (±6 month). The test population encompassed 108 male examinees. The relation between the longitudinal anthropometric dimensions and the results achieved in shot put and javelin throw are presented via predictor system - body height, sitting height, body weight, arm range, arm length, upper arm length, forearm length, hand length, leg length, upper leg length, lower leg length and two criteria systems: results achieved in shot put was one and result achieved in javelin throw was the other. The applied regression analysis showed that there was a statistically significant importance on a level 0.01 in six anthropometric dimensions – sitting height, arm range, arm length, leg length, upper leg length, lower leg length and results achieved in shot put, but there was only one variable that had a statistically significant importance on a level 0.05 with results achieved in javelin throw – sitting height. This research has shown that each of these anthropometric dimensions may be decisive for the accomplishment of a better result. Choosing of this way we can select those children that have a solid base to start the training techniques of the shot put and javelin throw, what will help reduce loss of time and the energy.